2014
DOI: 10.1002/cncy.21449
|View full text |Cite
|
Sign up to set email alerts
|

The value of the “suspicious for urothelial carcinoma” cytology category: A correlative study of 4 years including 337 patients

Abstract: BACKGROUND:The terminology used in reporting urine cytology lacks uniformity and the significance of the "atypical"and "suspicious" categories is still not well established. This results in variable clinical follow-up and management of those cases. The authors sought to investigate the prognostic value of a diagnosis of "suspicious for high-grade urothelial carcinoma" (HGUCA). METHODS: All cases with a "suspicious" or "positive" cytological diagnosis spanning 4 years were included and correlated with the subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
2
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 17 publications
0
15
2
2
Order By: Relevance
“…The results from our study are a useful baseline from which we can determine the changes that the introduction of the rigorously defined diagnostic categories of TPS will bring. Surprisingly, our results are closer to those obtained by Papanicolaou and collaborators in 1958 than to those obtained by more recent studies, which reported either lower or much higher PPV values. This most likely reflects differences in criteria used by different institutions and cytopathologists; although it also may reflect diverse patient populations, clinical practice patterns, types of samples examined (voided urine vs instrumented urine), and cytopreparatory methods.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The results from our study are a useful baseline from which we can determine the changes that the introduction of the rigorously defined diagnostic categories of TPS will bring. Surprisingly, our results are closer to those obtained by Papanicolaou and collaborators in 1958 than to those obtained by more recent studies, which reported either lower or much higher PPV values. This most likely reflects differences in criteria used by different institutions and cytopathologists; although it also may reflect diverse patient populations, clinical practice patterns, types of samples examined (voided urine vs instrumented urine), and cytopreparatory methods.…”
Section: Discussioncontrasting
confidence: 99%
“…Despite having undergone multiple revisions since these first studies regarding UCyt, the diagnostic category of “suspicious” continued to suffer from vague definitions and variable predictive values, resulting in a perceived disconnect between pathologists and clinicians regarding proper follow‐up. The classification scheme proposed by the Papanicolaou Society of Cytopathology Practice Guidelines Task Force in 2004 avoided a diagnosis of suspicious entirely, instead grouping all equivocal results into 1 category titled “atypical.” Before the publication of TPS, several recently published studies reviewed their authors' experience with the diagnosis of “suspicious” and included an analysis of cytomorphologic criteria used to establish the diagnosis of “suspicious for urothelial carcinoma” or its equivalent, “atypical urothelial cells, cannot exclude high‐grade urothelial carcinoma (AUC‐H)” (Table ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Morphologists are trained that a high N:C ratio is a worrisome feature but to our knowledge the exact ratio at which a cell becomes atypical is never defined and is dependent on many factors, including tissue type, preparation, inflammation, etc. In the pathology literature, algorithmic systems for determining malignant potential often make reference to an increased N:C ratio and some go so far as to define a specific decimal ratio (as in the Paris system for urinary cytopathology) or range . However, it is typically not revealed how, or even if, this ratio was determined (eg, by micrometer, computer‐aided analysis, or estimation).…”
Section: Introductionmentioning
confidence: 99%